EFFECT OF DIFFERENT COLORS OF UNDERWATERLAMPTO CATCH USE KELONG (LIFT NET) IN PENAAH VILLAGE DISTRICT SENAYANG LINGGA REGENCY PROVINCE KEPULAUAN RIAU - Riki Saputra; Bustari Bustari; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted in the dark moon in Mei 2017 In Penaah Village District Senayang Lingga Regency Province Kepulauan Riau. Most of lift net fishermen in Penaah vilageconduted fishing byusing petromax lamp fishing gear. The objective of the research is to understand the effect of light colors distinchen  towards fish catch and its fish species.The method in this researchby using Experimental. The treatment of light color are transparent color, blue color and yellow colorfor three Lift Net’s. The species caught are anchovies (Stolephorus commersoni) (137,9 kg), Yellowstripe Scad(Selaroides leptolepis)(47,1 kg) squid (Loligo sp) (38 kg), FringescaleSardinella(Sardinella fimbriata) (33,4 kg), cuttlefish(Sepia.sp) (18,9 kg), Great Barracuda(Sphyraena sp) (10,3 kg), Orangefin Ponyfish(Leiognathus sp) (1,6 kg) and Tropical Silverside(Atherinomorus sp) (1 kg). The results showed that of analisis of variance have significant effect on the color of the light weight of the total catch. In the operation of the fishing gear underwaterlamp blue light is more effective than a transparent color underwaterlamp  and yellow colorunderwaterlamp.Keywords: Lift net, penaahvillage, light color